The Meaning of Social Support for Mental Health Service-Users: The Case Managers' Perspective. - Fitzgerald, Sandra; Chronister, Julie; Zheng, Qi Michael; Chou, Chih-Chin (Community Mental Health Journal, 2025)
This study sought to understand the unique types of social support salient to mental health service-users from the perspective of case managers. The sample consisted of case managers working in county mental health agencies in the southwest and west coast. Data was gathered from three focus groups and analyzed using NVivo 10 and Consensual Qualitative Research. Six themes were described including relational support, consistency support, validation and affirmation support, social connection support, day-to-day living support and vocational support. While the social support domains described in this study share conceptual underpinnings with traditional conceptualizations of support, our findings reveal unique types of support from the perspective of case managers. Findings from this study offer an important perspective—case managers—to the extant body of research investigating the meaning of social support for people with lived mental health experiences. Of particular interest is the finding that relational support, affirmative and validation support, and consistency support are salient case manager functions.